50 años de relaciones entre España y Estados Unidos - Niño, Antonio (Cuadernos de Historia Contemporánea, 2003)
Pro-United States position, adopted by Spanish diplomacy during the Iraqi crisis generated a strong controversy in Spanish Society. This work tries to summarize the arguments fistated by pro atlantic and pro-european people, and to examine their vision about the relations between Spain and the United States, since the agreement of 1953. Finally, those relations are analyzed from a historic point of view, and questions to be resolved by future researches are set out.